Monocytes are the predominate cell type associated with Listeria monocytogenes in the gut but they do not serve as an intracellular growth niche - Jones, Grant S. (J Immunol, 2017)
After foodborne transmission of the facultative intracellular bacterial pathogen Listeria monocytogenes, most of the bacterial burden in the gut is extracellular. However, we previously demonstrated that intracellular replication in an as yet unidentified cell type was essential for dissemination and systemic spread of L. monocytogenes. Here, we show that the vast majority of cell-associated L. monocytogenes in the gut were adhered to Ly6C(hi) monocytes, a cell type that inefficiently internalized L. monocytogenes. With bone marrow-derived in vitro cultures, high multiplicity of infection (MOI) or the use of opsonized bacteria enhanced uptake of L. monocytogenes in CD64-negative monocytes, but very few bacteria reached the cell cytosol. Surprisingly, monocytes that had up-regulated CD64 expression in transition towards becoming macrophages fully supported intracellular growth of L. monocytogenes. In contrast, “inflammatory” monocytes that increased CD64 expression in the bone marrow of BALB/c/By/J mice prior to L. monocytogenes exposure in the gut did not support L. monocytogenes growth. Thus, contrary to the perception that L. monocytogenes can infect virtually all cell types, neither naïve nor inflammatory Ly6C(hi) monocytes served as a productive intracellular growth niche for L. monocytogenes. These results have broad implications for innate immune recognition of L. monocytogenes in the gut and highlight the need for additional studies on the interaction of extracellular, adherent L. monocytogenes with the unique subsets of myeloid-derived inflammatory cells that infiltrate sites of infection.